Starfish skeleton bionic scaffold as well as preparation method and application thereof
The preparation of starfish bone bionic scaffolds through electrospinning technology, combined with modified chitosan hydrogel, solved the problem of insufficient mechanical strength and biological activity of existing bone regeneration scaffolds, achieved higher mechanical properties and osteoinduction capabilities, and provided a new strategy for bone defect repair.
Patent Information
- Application Number
- CN202411787504.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing bone regeneration scaffolds have shortcomings in terms of mechanical strength and biological activity, and it is difficult to effectively solve the difficulty of regeneration of bone defects.
Nanofibers were prepared by electrospinning technology, simulated the skeleton structure of starfish, mineralized in simulated body fluids, and combined with modified chitosan hydrogel, a scaffold with bionic structure of starfish bones was prepared.
The mechanical properties and osteoinduction capabilities of the stent are improved, and new bone tissue engineering strategies are provided, providing a more reliable solution for clinical treatment of bone defect repair.
Smart Images

Figure CN119746150A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomaterials, and in particular relates to a starfish skeleton bionic scaffold and a preparation method and application thereof. Background Art
[0002] In recent years, bone defects caused by trauma, surgery, and genetic diseases have increased dramatically. The treatment of bone defects, especially those of critical size, presents significant challenges. Currently, autologous bone transplantation and allogeneic bone transplantation are considered the "gold standard" for treatment. However, these treatments also have disadvantages, such as limited autologous graft donors and limitations such as infection during treatment, leading to serious complications at the donor site. The application of allogeneic bone transplantation is hampered by the risk of disease transmission and the difficulty of allogeneic bone integrating with host tissue. Therefore, more reliable and stable treatment methods are urgently needed to solve the difficulty of bone defect regeneration. With the development of tissue engineering, new strategies and means have been provided for the treatment of bone defects, but there are the following two problems: (1) mechanical mismatch; (2) low bioactivity. Therefore, the development of bone regeneration scaffolds with mechanical adaptation and improved osteoinduction ability is of great significance for bone defect repair.
[0003] Hydrogel is a three-dimensional porous mesh gel with rich water absorption, good biocompatibility and degradable structure. Chitosan is derived from deacetylated chitosan and is the second largest natural renewable polymer material in nature after cellulose. The natural polymer chitosan has excellent properties such as biodegradability, biocompatibility, and good antibacterial properties, and is widely used in the biomedical field.
[0004] However, due to its low water solubility and only being soluble in acidic solutions, the application of chitosan-based hydrogels in the biomedical field is limited. Acrylic or methacrylic chitosan (CS-MA) is often used to prepare photocrosslinked hydrogels, but it usually requires the addition of photoinitiators, which may introduce potential cytotoxicity. In addition, pure hydrogels do not have sufficient mechanical strength, which limits their application in bone tissue engineering.
[0005] At present, bionic strategies play an important role in materials science and are widely used in fields such as biomedicine. Starfish is an echinoderm, characterized by a body composed of many calcareous bone plates connected by connective tissue. Studies have found that the skeleton of a starfish is composed of countless "small bones" with a diameter of only a few millimeters. These small bones are connected to soft tissues with a porous structure and eventually form the overall skeleton of the starfish. This structure allows the starfish to strengthen the bones in specific directions, making them both flexible and strong, thereby improving mechanical properties. This structure is rare in nature, and it is currently impossible to synthesize this structure artificially under mild conditions. Summary of the invention
[0006] The purpose of the present invention is to provide a starfish skeleton bionic scaffold and its preparation method and application in order to solve at least one of the above problems, so as to solve the problem of insufficient mechanical strength of hydrogel in the prior art. This scheme realizes the preparation of starfish skeleton bionic scaffold, exerts the synergistic effect of mechanical adaptation and osteogenesis, and provides a new bone tissue engineering strategy for the clinical treatment of bone defect repair.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The first aspect of the present invention discloses a method for preparing a starfish skeleton bionic scaffold, comprising the following steps:
[0009] Firstly, nanofibers of bionic starfish porous soft tissue are prepared by electrospinning technology; then, they are mineralized in simulated body fluid to obtain nanofibers with surface bionic starfish skeletons; finally, they are combined with chitosan hydrogel to obtain the starfish skeleton bionic scaffold.
[0010] Preferably, the method comprises the following steps:
[0011] (1) preparing a chitosan acetic acid solution and a thioctic acid ethanol solution respectively, adding a catalyst to the thioctic acid ethanol solution, then mixing the chitosan acetic acid solution and the thioctic acid ethanol solution, dialysis purification and freeze drying to obtain modified chitosan;
[0012] (2) preparing a hexafluoroisopropanol solution containing dissolved microspheres, and electrospinning to obtain a nanofiber membrane; dispersing the nanofiber membrane in tert-butyl alcohol, and homogenizing to obtain a nanofiber dispersion;
[0013] (3) immersing the nanofiber dispersion prepared in step (2) in a sodium hydroxide solution to generate carboxyl groups on the surface of the nanofiber dispersion, and then washing to remove residual sodium hydroxide;
[0014] (4) placing the nanofiber dispersion treated in step (3) in SBF simulated body fluid for mineralization;
[0015] (5) preparing a modified chitosan aqueous solution, adding the nanofiber dispersion after mineralization in step (4) to the modified chitosan aqueous solution to obtain a bionic scaffold precursor solution, and then obtaining the starfish skeleton bionic scaffold by photocrosslinking and freeze-drying.
[0016] Preferably, in step (1), the ratio of chitosan to lipoic acid is 1.5 g: 1-5 mmol, the catalyst is one or a combination of two of LAP, NHS and EDC, and the dialysis purification time is 1-6 days.
[0017] Specifically, the catalyst is selected as LAP or NHS+EDC.
[0018] Preferably, in step (2), the microspheres include PLA, PCL and PLGA, and the mass concentration of the microspheres in the hexafluoroisopropanol solution containing the microspheres is 10-20%.
[0019] Preferably, in step (3), the concentration of sodium hydroxide is 0.01-0.2 mol / L, and the soaking time is 2-20 min.
[0020] Preferably, in step (4), the SBF simulated body fluid is 1×-10×SBF simulated body fluid, and the mineralization time is 0-24h.
[0021] Preferably, in step (5), the mass ratio of the modified chitosan to the nanofiber dispersion is 1-3:3-6, and the photocrosslinking is performed under ultraviolet light with a wavelength of 405 nm.
[0022] Preferably, the method comprises the following steps:
[0023] (1) preparing 1.5 g / 60 mL chitosan acetic acid solution and 2 mmol / 30 mL thioctic acid ethanol solution respectively, adding EDC and NHS as catalysts to the thioctic acid ethanol solution, then mixing the chitosan acetic acid solution and the thioctic acid ethanol solution and stirring for 4 h, dialysis purification and freeze drying for 5 days to obtain modified chitosan;
[0024] (2) preparing a 1.5 g / 10 mL hexafluoroisopropanol solution containing dissolved microspheres, and electrospinning to obtain a nanofiber membrane; dispersing the nanofiber membrane in tert-butyl alcohol, and homogenizing to obtain a nanofiber dispersion;
[0025] (3) soaking the nanofiber dispersion prepared in step (2) in a 0.1 mol / L sodium hydroxide solution for 15 min to generate carboxyl groups on the surface of the nanofiber dispersion, and then washing with deionized water to remove residual sodium hydroxide;
[0026] (4) placing the nanofiber dispersion treated in step (3) in 10×SBF simulated body fluid for mineralization for 30 min-2 h;
[0027] (5) preparing a modified chitosan aqueous solution with a mass concentration of 2%, adding the nanofiber dispersion after mineralization in step (4) to the modified chitosan aqueous solution so that the mass concentration of the mineralized nanofiber dispersion is 5%, and obtaining a bionic scaffold precursor solution, followed by photo-crosslinking with ultraviolet light of a wavelength of 405 nm and freeze-drying to obtain the starfish skeleton bionic scaffold.
[0028] The second aspect of the present invention discloses a starfish skeleton bionic scaffold obtained by any of the above-mentioned preparation methods.
[0029] The third aspect of the present invention discloses an application of the starfish skeleton bionic scaffold as described above in the field of bone defect repair.
[0030] The working principle of the present invention is:
[0031] We enhanced the mechanical strength of hydrogels by mimicking the skeletal structure of starfish. First, we prepared polylactic acid nanofibers through electrospinning technology to mimic the porous soft tissue of starfish; then, we mineralized it in simulated body fluids to bind the mineralized substance hydroxyapatite on its surface to mimic the skeleton of starfish; finally, we combined it with chitosan hydrogel to mimic the overall skeletal structure of starfish through this soft-hard combination. We speculate that the scaffold prepared by mineralized nanofibers can enhance its mechanical properties, and as the hydrogel degrades, hydroxyapatite is released, thereby improving bone inductivity and playing a role in promoting bone formation.
[0032] Furthermore, due to the presence of amino and hydroxyl reactive groups in chitosan, we modified the hydrogel to obtain a hydrogel that can self-photocrosslink without the need for a photoinitiator.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention discloses a starfish skeleton bionic scaffold, a preparation method and an application. First, a modified photo-crosslinked chitosan hydrogel and a nanofiber having a starfish skeleton structure are prepared by the method disclosed in the present application; then, the nanofiber and the hydrogel are mixed to prepare a bionic scaffold. The addition of nanofibers modified with a bionic structure improves the mechanical properties of the scaffold to meet the requirements of tissue regeneration, and at the same time, the osteogenic effect of the mineralized hydroxyapatite is utilized to promote bone regeneration, thereby providing a new bone tissue engineering strategy for the clinical treatment of bone defect repair.
[0035] 2. The overall implementation process of this method is relatively simple, with a wide range of sources, strong operability, great market application potential, and is conducive to promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the optimal synthesis of the starfish skeleton bionic scaffold;
[0037] Figure 2 Schematic diagram (A) and Fourier transform infrared spectrum (B) of the photo-crosslinked chitosan hydrogel (CSA) in Example 1;
[0038] Figure 3 The preparation and characterization of the starfish skeleton bionic scaffold in Example 7, A is the XRD pattern (200nm), B is the FTIR pattern, C is the transmission electron microscope pattern, D is the physical image of CP and CPF3, and E is the mechanical characterization result;
[0039] Figure 4The results of the biocompatibility activity of CPS on BMSCs cells in Experimental Example 1, A is the result of CCK-8 experiment, and B is the result of live-dead staining experiment;
[0040] Figure 5 This is the evaluation of the effect of CPS in promoting osteogenic differentiation of BMSCs in Experimental Example 2. A is the ALP staining result, and B is the expression of osteogenesis-related genes. DETAILED DESCRIPTION
[0041] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0042] In the following description, unless otherwise specified, the reagents used are conventional commercially available products, and the methods used are well known in the art.
[0043] The present invention provides a starfish skeleton bionic scaffold, a preparation method and an application thereof, studies the mechanical adaptation structure-activity relationship of the starfish skeleton bionic scaffold, and utilizes the osteogenesis effect of hydroxyapatite formed by mineralization to prepare a starfish skeleton bionic scaffold, exerts the synergistic effect of mechanical adaptation and osteogenesis, and provides a new bone tissue engineering strategy for the clinical treatment of bone defect repair.
[0044] A preparation method and application of a starfish skeleton bionic scaffold, comprising the following steps:
[0045] (1) Dissolve chitosan in acetic acid solution and stir to prepare solution A; dissolve lipoic acid in ethanol solution, add LAP or EDC and NHS to the solution in sequence and stir to prepare solution B.
[0046] (2) under magnetic stirring, adding the solution B in step (1) to the solution A, stirring to prepare the solution C, and finally, purifying the solution C by dialyzing with a dialysis tube and freeze-drying to obtain the modified chitosan (CSA) for further use.
[0047] (3) Add microspheres of PLA, PCL or PLGA to hexafluoroisopropanol (HFIP) and stir to prepare solution D. Load solution D into a 5 mL syringe and electrospin to obtain nanofiber membranes of PLA, PCL or PLGA. Cut the nanofiber membranes of PLA, PCL or PLGA into small pieces, disperse them in tert-butyl alcohol, and homogenize them with a high-speed homogenizer to obtain a uniform nanofiber dispersion.
[0048] (4) Immersing the uniform nanofiber dispersion in step (3) in a 0.01-0.2 mol / L sodium hydroxide solution to generate carboxyl groups (-COOH) on its surface to varying degrees, and washing the residual sodium hydroxide with deionized water.
[0049] (5) The nanofiber dispersion in step (4) is placed in 1× to 10× SBF and mineralized at room temperature.
[0050] (6) dissolving the modified chitosan (CSA) in step (2) in deionized water to prepare solution E;
[0051] (7) Adding the mineralized nanofiber dispersion in step (5) to solution E to obtain a starfish skeleton bionic scaffold (CPF) mixed solution, cross-linking and freeze-drying under ultraviolet light of 405 nm wavelength to prepare a CPF composite scaffold.
[0052] in,
[0053] The molar amount of lipoic acid in step (1) is between 1-5 mmol.
[0054] In the step (2), solution B is added to solution A and the stirring time is between 4 and 12 hours.
[0055] The time for dialyzing the purified solution C using the dialysis tube in step (2) is between 1 and 6 days.
[0056] The mass concentration percentage of PLA, PCL or PLGA in the solution D obtained in the step (3) is between 10-20%.
[0057] The concentration of the sodium hydroxide solution used to immerse the nanofiber dispersion in step (4) is between 0.05 and 0.2 mol / L.
[0058] In the step (4), the uniform nanofiber dispersion is immersed in the sodium hydroxide solution for a period of 2-20 minutes.
[0059] The mineralization time of the nanofiber dispersion in step (5) is between 0 and 24 hours.
[0060] The mass concentration percentage of modified chitosan (CSA) in the solution E obtained in the step (6) is between 1-3%.
[0061] The mass concentration percentage of the nanofiber dispersion added to the modified chitosan aqueous solution in step (7) is between 3-6%.
[0062] Further preferably, Figure 1 As shown, the following steps are included:
[0063] (1) Dissolve chitosan in acetic acid solution and stir to prepare solution A; dissolve lipoic acid in ethanol solution, add EDC and NHS to the solution in sequence and stir to prepare solution B.
[0064] (2) under magnetic stirring, adding the solution B in step (1) to the solution A, stirring to prepare the solution C, and finally, purifying the solution C by dialyzing with a dialysis tube and freeze-drying to obtain the modified chitosan (CSA) for further use.
[0065] (3) PLA microspheres were added to hexafluoroisopropanol (HFIP) and stirred to prepare solution D. Solution D was loaded into a 5 mL syringe and electrospun to obtain a PLA nanofiber membrane. The PLA nanofiber membrane was cut into small pieces, dispersed in tert-butyl alcohol, and homogenized with a high-speed homogenizer to obtain a uniform nanofiber dispersion.
[0066] (4) Immersing the uniform nanofiber dispersion in step (3) in a sodium hydroxide solution to generate carboxyl groups (-COOH), and washing the residual sodium hydroxide with deionized water.
[0067] (5) The nanofiber dispersion in step (4) is placed in 10×SBF for mineralization at room temperature.
[0068] (6) dissolving the modified chitosan (CSA) in step (2) in deionized water to prepare solution E;
[0069] (7) Adding the mineralized nanofiber dispersion in step (5) to solution E to obtain a CPF mixed solution, cross-linking and freeze-drying under ultraviolet light of 405 nm wavelength to prepare a CPF composite scaffold.
[0070] in,
[0071] The molar amount of lipoic acid in the step (1) is 2 mmol.
[0072] In the step (2), solution B is added to solution A and the stirring time is 4 hours.
[0073] The time for dialysis purification of solution C using dialysis tube in step (2) is 5 days.
[0074] The mass concentration percentage of PLA in the solution D obtained in the step (3) is 15%.
[0075] The concentration of the sodium hydroxide solution used to immerse the nanofiber dispersion in step (4) is 0.1 mol / L.
[0076] In the step (4), the uniform nanofiber dispersion is immersed in the sodium hydroxide solution for 15 minutes.
[0077] The mineralization time of the nanofiber dispersion in step (5) is 30 min, 1 h and 2 h respectively.
[0078] The mass concentration percentage of modified chitosan (CSA) in the solution E obtained in the step (6) is 2%.
[0079] The mass concentration of the nanofiber dispersion added to the modified chitosan aqueous solution in step (7) is 5%.
[0080] Example 1
[0081] This embodiment provides a method for preparing chitosan hydrogel (CSA) capable of self-photocrosslinking (modification).
[0082] The specific synthesis method of the self-photocrosslinked chitosan hydrogel (CSA) is as follows:
[0083] (1) 1.5 g of chitosan (CS) was dissolved in 60 mL of acetic acid solution and stirred for 1 h to prepare solution A. 0.42 g (about 2 mmol) of lipoic acid (LA) was dissolved in 30 mL of ethanol solution and stirred for 5 min. 0.39 g of EDC and 0.23 g of NHS were added to the solution in sequence to catalyze the reaction for 1 h to prepare solution B.
[0084] (2) Under magnetic stirring, solution B was added to solution A, followed by stirring for 4 h. Finally, the reactant was purified by dialysis using a dialysis tube for 5 days and freeze-dried to obtain CSA for further use.
[0085] (3) The molecular structure of CSA was tested using Fourier transform infrared spectroscopy (FTIR). Figure 2 shown.
[0086] (4) In order to evaluate the photocrosslinking performance of chitosan hydrogel, 0.2 g CSA was dissolved in 5 mL deionized water to prepare a CSA prepolymer solution. The prepolymer solution was transferred to a round-bottom glass bottle, which was tilted and placed under ultraviolet light (405 nm, 283 mW / cm 2 ) After irradiation for 20 seconds, the flow of the hydrogel was observed to preliminarily evaluate the photocrosslinking performance of the CSA.
[0087] Depend on Figure 2 A shows that in the infrared spectrum, CSA is at 558cm -1 There is a characteristic infrared absorption peak of disulfide bond at 1644cm -1 and 1555cm -1 There are also obvious absorption peaks at 1646cm -1 The characteristic absorption of the carbonyl group of the amide bond is 1548 cm -1 is the characteristic absorption of CN, while CS has no obvious characteristic absorption at the same position. Figure 2B shows that the CSA hydrogel prepolymer solution is a flowing transparent liquid before irradiation, and becomes a transparent gel after irradiation with ultraviolet light of wavelength 405nm for 20 seconds. The above results prove that LA and CS are successfully combined to prepare photo-crosslinked chitosan hydrogel (CSA).
[0088] Example 2
[0089] This embodiment provides a method for preparing chitosan hydrogel (CSA) capable of self-photocrosslinking (modification).
[0090] This example is basically the same as Example 1, except that 0.21 g (about 1 mmol) of lipoic acid (LA) is dissolved in 30 mL of ethanol solution.
[0091] The performance of the obtained product is basically consistent with that of Example 1.
[0092] Example 3
[0093] This embodiment provides a method for preparing chitosan hydrogel (CSA) capable of self-photocrosslinking (modification).
[0094] This example is basically the same as Example 1, except that 1.03 g (about 5 mmol) of lipoic acid (LA) is dissolved in 30 mL of ethanol solution.
[0095] The performance of the obtained product is basically consistent with that of Example 1.
[0096] Example 4
[0097] This embodiment provides a method for preparing chitosan hydrogel (CSA) capable of self-photocrosslinking (modification).
[0098] This example is basically the same as Example 1, except that LAP is added to solution B.
[0099] The performance of the obtained product is basically consistent with that of Example 1.
[0100] Example 5
[0101] This embodiment provides a method for preparing chitosan hydrogel (CSA) capable of self-photocrosslinking (modification).
[0102] This embodiment is basically the same as embodiment 1, except that the dialysis purification time is 1 day.
[0103] The performance of the obtained product is basically consistent with that of Example 1.
[0104] Example 6
[0105] This embodiment provides a method for preparing chitosan hydrogel (CSA) capable of self-photocrosslinking (modification).
[0106] This embodiment is basically the same as embodiment 1, except that the dialysis purification time is 6 days.
[0107] The performance of the obtained product is basically consistent with that of Example 1.
[0108] Example 7
[0109] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0110] The specific synthesis method of the starfish skeleton bionic scaffold is as follows:
[0111] (1) 1.5 g of PLA microspheres were added to 10 mL of hexafluoroisopropanol (HFIP) and stirred at room temperature for 12 hours. The homogeneous solution was loaded into a 5 mL syringe and electrospun at 18 kV, 1 mL / h, and a relative humidity of 40 ± 5%. The PLA nanofiber membrane obtained by spinning was cut into small pieces, dispersed in tert-butyl alcohol, and homogenized with a high-speed homogenizer for at least 30 minutes to obtain a uniform nanofiber dispersion.
[0112] (2) The uniform nanofiber dispersion was immersed in a 0.1 mol / L sodium hydroxide solution for 15 minutes to generate carboxyl groups (-COOH), and the residual sodium hydroxide was washed with deionized water. Then, the obtained nanofiber dispersion was placed in 10×SBF and mineralized at room temperature for 30 min, 1 h, and 2 h, respectively.
[0113] (3) The nanofiber dispersions mineralized for 30 min, 1 h, and 2 h were added to the CSA solution prepared in Example 1 to obtain CPF mixed solutions (the mass concentration of the nanofiber dispersion was 5%, and the mass concentration of the modified chitosan was 2%), which were cross-linked and freeze-dried under ultraviolet light with a wavelength of 405 nm to prepare CPF composite scaffolds, which were named CPF1, CPF2, and CPF3, respectively. At the same time, the untreated nanofiber dispersion was added to the CSA solution to obtain a CP mixed solution, which was cross-linked and freeze-dried under ultraviolet light with a wavelength of 405 nm to prepare a CP composite scaffold.
[0114] (4) Transmission electron microscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray diffractometer (XRD) were used to test the morphology and structure of the mineralized material on the nanofibers. Figure 3 shown.
[0115] Depend on Figure 3 A shows that the nanofibers with different mineralization times are loaded with minerals, and the proportion of loaded minerals varies with the mineralization time. Figure 3 B and 3C show that in the infrared spectrum, CPF3 is at 558cm -1The characteristic peak at 1643 cm -1 and 3362cm -1 There are also obvious absorption peaks at 1643cm -1 It is the characteristic absorption of C=O, 3362cm -1 is the stretching vibration of OH, indicating the presence of HA on the nanofibers after mineralization. XRD analysis results show the presence of characteristic peaks of hydroxyapatite in the mineralized nanofibers. These peaks appear at angles of approximately 26° and 32° and correspond to diffraction (002) and (211), which are missing in the PLA sample. These results indicate that hydroxyapatite was successfully formed on the PLA nanofibers by mineralization. Finally, by Figure 3 E It can be seen that the mechanical test showed that the CPF3 group had the best mechanical properties compared with the CPF1 and CPF2 groups, so CPF3 was selected for subsequent experiments and named CPS.
[0116] Example 8
[0117] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0118] This embodiment is basically the same as Embodiment 7, except that PCL microspheres are used with a mass concentration of 10% (ie, 1 g of PCL microspheres is added to 10 mL of hexafluoroisopropanol (HFIP)).
[0119] The performance of the obtained product is similar to that of Example 7.
[0120] Example 9
[0121] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0122] This example is basically the same as Example 7, except that PLGA microspheres are used with a mass concentration of 20% (ie, 2 g of PLGA microspheres are added to 10 mL of hexafluoroisopropanol (HFIP)).
[0123] The performance of the obtained product is similar to that of Example 7.
[0124] Example 10
[0125] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0126] This embodiment is basically the same as Embodiment 7, except that the concentration of sodium hydroxide is 0.01 mol / L and the soaking time is 20 min.
[0127] The performance of the obtained product is similar to that of Example 7.
[0128] Embodiment 11
[0129] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0130] This embodiment is basically the same as Embodiment 7, except that the concentration of sodium hydroxide is 0.2 mol / L and the soaking time is 2 min.
[0131] The performance of the obtained product is similar to that of Example 7.
[0132] Example 12
[0133] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0134] This example is basically the same as Example 7, except that the obtained nanofiber dispersion is placed in 1×SBF and mineralized at room temperature for 24 hours.
[0135] The performance of the obtained product is similar to that of Example 7.
[0136] Embodiment 13
[0137] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0138] This example is basically the same as Example 7, except that the obtained nanofiber dispersion is placed in 5×SBF and mineralized at room temperature for 12 h.
[0139] The performance of the obtained product is similar to that of Example 7.
[0140] Embodiment 14
[0141] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0142] This embodiment is basically the same as Embodiment 7, except that in the CPF mixed solution, the mass concentration of the nanofiber dispersion is 3%, and the mass concentration of the modified chitosan is 1%.
[0143] The performance of the obtained product is similar to that of Example 7.
[0144] Embodiment 15
[0145] This embodiment provides a method for preparing a starfish skeleton bionic scaffold.
[0146] This embodiment is basically the same as Embodiment 7, except that in the CPF mixed solution, the mass concentration of the nanofiber dispersion is 6%, and the mass concentration of the modified chitosan is 3%.
[0147] The performance of the obtained product is similar to that of Example 7.
[0148] Test Example 1
[0149] In this test example, the in vitro biocompatibility of the biomimetic scaffold in Example 7 was evaluated by CCK-8 and live-dead staining.
[0150] The evaluation method of this embodiment is:
[0151] (1) Set the experimental groups as follows:
[0152] ①NC group: blank control group, without adding any materials / scaffolds;
[0153] ② CP group: CP composite scaffold prepared in Example 7;
[0154] ③CPS group: the starfish skeleton bionic scaffold CPS prepared in Example 7.
[0155] (2) CCK-8 test: The sterilized scaffolds were immersed in culture medium to obtain extracts for 1, 3, and 5 days. 3 The cells were evenly inoculated into 96-well culture plates at a density of 100 μg / well. After the cells adhered to the wall, the corresponding culture medium was replaced according to the experimental group and cultured in a 37°C, 5% CO2 incubator. On the 1st, 3rd and 5th days, the culture medium was removed, PBS was washed, 10% CCK-8 solution was added, and the cells were incubated in the incubator for 1 hour. The absorbance at 450 nm was then measured with an ELISA reader to detect the activity of BMSCs in each group. The results are shown in Figure 2. Figure 4 shown.
[0156] (3) Live-death staining: BMSCs were plated at 1×10 4 The cells were evenly seeded at a density of 100 μg / well in a 24-well culture plate. After the cells adhered to the wall, the corresponding culture medium was replaced according to the experimental group and continued to be cultured. On the third day, the culture medium was aspirated and washed with PBS. After incubation with the working solution for 15 minutes, the cells were washed twice with PBS. The live and dead staining of BMSCs was observed under a fluorescence microscope. The results are shown in Figure 2. Figure 4 shown.
[0157] Depend on Figure 4It can be seen that the results of the CCK-8 experiment showed that on the first day, there was no statistical difference between the CP group and the CPS group and the control group; on the 3rd and 5th days, the proliferation activity of BMSCs in the CP group and the CPS group increased significantly, and there was a statistical difference between them and the control group. In addition, the live-dead staining results on the 3rd day also showed that the BMSCs cultured in each group of scaffolds were spindle-shaped, with living cells dominating and only a few cells dying, showing good cell viability, indicating that each group of scaffolds had excellent biocompatibility. Compared with the control group, the number of live BMSCs in the CP group and the CPS group increased, and the number of dead cells was less. These results suggest that CP and CPS have good cell compatibility and can promote the proliferation of BMSCs to a certain extent.
[0158] Test Example 2
[0159] In this test example, ALP staining and RT-qPCR were used to evaluate the in vitro osteogenic performance of the scaffold in Example 7.
[0160] The evaluation method of this embodiment is:
[0161] (1) Alkaline Phosphatase (ALP) staining: BMSCs were cultured at 4×10 4 / well were inoculated in a 12-well plate, cultured for 24 hours until the cells adhered to the wall, and then replaced with the corresponding culture medium according to the experimental group and continued to culture. The medium was changed every 2 days for 7 days. On the 7th day, the culture medium was aspirated, washed 3 times with PBS, then fixed with 4% paraformaldehyde for 30 minutes, washed 3 times with PBS, added with ALP staining working solution, and incubated at room temperature in the dark for 30 minutes. After removing the staining working solution, wash twice with distilled water to terminate the color reaction, observe under a microscope and take pictures to record. The results are as follows Figure 5 shown.
[0162] (2) The Bio-Rad real-time quantitative reverse transcription-polymerase chain reaction (RT-qPCR) system was used to detect the expression of osteogenesis-related genes (Alp, ColI, Runx2, and Ocn). β-actin was used as the internal reference gene during the detection process, and the 2-ΔΔCT method was used to obtain the relative expression data. Figure 5 shown.
[0163] Depend on Figure 5It can be seen that the ALP staining results on the 7th day showed that compared with the control group, the ALP staining in the CPS group was positive, indicating that the CPS group has the potential to promote the differentiation of BMSCs into osteoblasts. After 7 days of culture of CP and CPS with BMSCs, the mRNA expression levels of BMSCs osteogenic differentiation-related genes were detected by RT-qPCR. Compared with the control group, the mRNA expression levels of Alp, ColI, Runx2 and Ocn in the CP group increased, but there was no statistical difference. In the CPS group, the mRNA expression levels of Alp, ColI, Runx2 and Ocn were significantly increased.
[0164] The above results indicate that CPS can promote the differentiation of BMSCs into osteoblasts and has good osteogenesis function.
[0165] In summary, the technical scheme of the present invention includes: first, preparing photo-crosslinked chitosan hydrogel and nanofibers with starfish bone structure by the method disclosed in the scheme; then, mixing the nanofibers with the hydrogel to prepare a bionic scaffold. Finally, the mechanical properties of the scaffold are improved by adding nanofibers modified with bionic structures to meet the requirements of tissue regeneration, while utilizing the osteogenic effect of mineralized hydroxyapatite to improve bone inductivity and promote bone regeneration, providing a new bone tissue engineering strategy for clinical treatment of bone defect repair.
[0166] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a starfish skeleton bionic scaffold, characterized in that: The steps include: Firstly, nanofibers of bionic starfish porous soft tissue are prepared by electrospinning technology; then, they are mineralized in simulated body fluid to obtain nanofibers with surface bionic starfish skeletons; finally, they are combined with chitosan hydrogel to obtain the starfish skeleton bionic scaffold.
2. The method for preparing a starfish skeleton bionic scaffold according to claim 1, characterized in that: The steps include: (1) preparing a chitosan acetic acid solution and a thioctic acid ethanol solution respectively, adding a catalyst to the thioctic acid ethanol solution, then mixing the chitosan acetic acid solution and the thioctic acid ethanol solution, dialysis purification and freeze drying to obtain modified chitosan; (2) preparing a hexafluoroisopropanol solution containing dissolved microspheres, and electrospinning to obtain a nanofiber membrane; dispersing the nanofiber membrane in tert-butyl alcohol, and homogenizing to obtain a nanofiber dispersion; (3) immersing the nanofiber dispersion prepared in step (2) in a sodium hydroxide solution to generate carboxyl groups on the surface of the nanofiber dispersion, and then washing to remove residual sodium hydroxide; (4) placing the nanofiber dispersion treated in step (3) in SBF simulated body fluid for mineralization; (5) preparing a modified chitosan aqueous solution, adding the nanofiber dispersion after mineralization in step (4) to the modified chitosan aqueous solution to obtain a bionic scaffold precursor solution, and then obtaining the starfish skeleton bionic scaffold by photocrosslinking and freeze-drying.
3. The method for preparing a starfish skeleton bionic scaffold according to claim 2, characterized in that: In step (1), the ratio of chitosan to lipoic acid is 1.5 g: 1-5 mmol, the catalyst is one or a combination of two of LAP, NHS and EDC, and the dialysis purification time is 1-6 days.
4. The method for preparing a starfish skeleton bionic scaffold according to claim 2, characterized in that: In step (2), the microspheres include PLA, PCL and PLGA, and the mass concentration of the microspheres in the hexafluoroisopropanol solution containing the microspheres is 10-20%.
5. The method for preparing a starfish skeleton bionic scaffold according to claim 2, characterized in that: In step (3), the concentration of sodium hydroxide is 0.01-0.2 mol / L, and the soaking time is 2-20 min.
6. The method for preparing a starfish skeleton bionic scaffold according to claim 2, characterized in that: In step (4), the SBF simulated body fluid is 1×-10×SBF simulated body fluid, and the mineralization time is 0-24h.
7. The method for preparing a starfish skeleton bionic scaffold according to claim 2, characterized in that: In step (5), the mass ratio of the modified chitosan to the nanofiber dispersion is 1-3:3-6, and the photocrosslinking is carried out under ultraviolet light with a wavelength of 405 nm.
8. The method for preparing a starfish skeleton bionic scaffold according to claim 1, characterized in that: The steps include: (1) preparing 1.5 g / 60 mL chitosan acetic acid solution and 2 mmol / 30 mL thioctic acid ethanol solution respectively, adding EDC and NHS as catalysts to the thioctic acid ethanol solution, then mixing the chitosan acetic acid solution and the thioctic acid ethanol solution and stirring for 4 h, dialysis purification and freeze drying for 5 days to obtain modified chitosan; (2) preparing a 1.5 g / 10 mL hexafluoroisopropanol solution containing dissolved microspheres, and electrospinning to obtain a nanofiber membrane; dispersing the nanofiber membrane in tert-butyl alcohol, and homogenizing to obtain a nanofiber dispersion; (3) soaking the nanofiber dispersion prepared in step (2) in a 0.1 mol / L sodium hydroxide solution for 15 min to generate carboxyl groups on the surface of the nanofiber dispersion, and then washing with deionized water to remove residual sodium hydroxide; (4) placing the nanofiber dispersion treated in step (3) in 10×SBF simulated body fluid for mineralization for 30 min-2 h; (5) preparing a modified chitosan aqueous solution with a mass concentration of 2%, adding the nanofiber dispersion after mineralization in step (4) to the modified chitosan aqueous solution so that the mass concentration of the mineralized nanofiber dispersion is 5%, and obtaining a bionic scaffold precursor solution, followed by photo-crosslinking with ultraviolet light of a wavelength of 405 nm and freeze-drying to obtain the starfish skeleton bionic scaffold.
9. A starfish skeleton bionic scaffold, characterized in that: The method is adopted as described in any one of claims 1 to 8.
10. Use of the starfish skeleton bionic scaffold as claimed in claim 9 in the field of bone defect repair.